VD_FINDINFO Décision / 2013 / 703 vom 28. März 2013 - VD Tribunal cantonal (2013)
RETRAITVOIE DE DROIT, INDEMNITÉEN GÉNÉRAL, AVOCAT D'OFFICE | 135 CPP (CH), 386 al. 2 let. a CPP (CH), 401 al. 3 CPP (CH)